Analysis Of Operational Cost Budget As A Planning Tool In PTPN III (Persero) KBDSL - Rahmat Daim Harahap; Novia Ardhya Garini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to determine how to use the operational cost budget as a planning tool at PTPN III(Persero) KBDSL. In this study the authors used a qualitative descriptive method. The results showed that in the preparation of the operational cost budget at PTPN III (Persero) KBDSL already used the Top down and Bottom up method, namely the role of each part in preparing the operational cost budget by involving several staff or employees from various fields by mobilizingtheir abilities. and their respective responsibilities. All operational costs of PTPN III (Persero) KBDSLin 2021, experienced a favorable variance, so that the budget as a planning tool has been very good. This is because the company has followed procedures with central company policies (directors).